Lighting Dynamics for Emotional Perception: A Technology-Driven Virtual Simulation Approach - Prasetyo, Didit; Ramadhani, Nugrahardi; Hariadi, Mochamad; Rizky Mutiaz, Intan (Engineering, Technology & Applied Science Research, 2025)
This research examines the effects of light color (Light Color), light intensity (Intensity), and time (Time) on emotional responses through a simulation created with the Unreal Engine. The controlled experiment carried out included 162 participants, the emotional perception of whom was assessed following scenarios with differing lighting conditions. The two-way ANOVA results revealed the significant influence of Light Color, Intensity, and Time (p < 0.001), along with that of the Light Color-Intensity and Intensity-Time interactions on human perception. The fuzzy logic examinations demonstrated that warm, low-intensity lighting during the day yields the highest perception score (7.8), while cold (cool), high-intensity lighting at night produces the lowest (3.6). The predictive regression model achieved a good accuracy (R² = 0.96), showing that the ideal lighting combination improves emotional experience. This research provides novel perspectives on dynamic lighting design for cinematography, gaming, and immersive media. However, further research is required to scale these findings on a wider population and diverse spatial environments.